2008
DOI: 10.2214/ajr.07.2441
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of CT-Guided Core Biopsy of Ground-Glass Opacity Pulmonary Lesions

Abstract: malignant disease is greater than 80% and 90%, respectively [10-16]. However, to our knowledge, the accuracy of CT-guided core biopsy of GGO lesions has not been reported in detail. Thus, the purpose of this study was to evaluate the diagnostic accuracy of CTguided core biopsy of GGO lesions. Materials and Methods Our institutional review board approved this study and waived informed patient consent. Study Population and Biopsy Indication We retrospectively reviewed the medical and imaging records of all patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 45 publications
3
56
1
Order By: Relevance
“…90%, regardless of nodule size or extent of the ground glass component. 162 In another small study of 40 individuals with subsolid nodules, the diagnostic yield of CT scan-guided core needle biopsy was 84% (16 of 19), but two of three individuals with nondiagnostic results were subsequently found to have cancer. 163 Hence, although TTNB appears to be less sensitive for subsolid than for solid nodules, it is still potentially useful, particularly for individuals who are at higher risk for surgical complications and those who wish to confi rm malignancy before undergoing surgical resection.…”
Section: Role Of Nonsurgical Biopsymentioning
confidence: 98%
“…90%, regardless of nodule size or extent of the ground glass component. 162 In another small study of 40 individuals with subsolid nodules, the diagnostic yield of CT scan-guided core needle biopsy was 84% (16 of 19), but two of three individuals with nondiagnostic results were subsequently found to have cancer. 163 Hence, although TTNB appears to be less sensitive for subsolid than for solid nodules, it is still potentially useful, particularly for individuals who are at higher risk for surgical complications and those who wish to confi rm malignancy before undergoing surgical resection.…”
Section: Role Of Nonsurgical Biopsymentioning
confidence: 98%
“…Notably, the diagnostic accuracy of CT fluoroscopy-guided needle aspiration or core biopsy for pure GGNs was lower than that for part-solid GGNs (45,49), which would be due to the low cellularity of pure GGNs (45). However, Kim et al (46), using CT-guided core biopsy, reported conflicting results that the diagnostic accuracy was not influenced by the proportion of the GGO component. We do not currently have a definite conclusion on whether biopsy would provide accurate diagnosis for SSNs.…”
Section: Imaging-guided Biopsy Of Subsolid Nodulesmentioning
confidence: 99%
“…With respect to the biopsy of SSNs, several CT-based approaches including sequential CT-guided-biopsy, CT fluoroscopy-guided biopsy, and cone-beam CT (CBCT) virtual-navigation-guided biopsy have been introduced (45)(46)(47)(48)(49). Either a fine needle aspiration biopsy or a core biopsy can be used, but core biopsy showed higher diagnostic accuracy (46,49).…”
Section: Imaging-guided Biopsy Of Subsolid Nodulesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the diagnostic sensitivity of CTNB ranges from 64% to 93% and the complication rate is relatively high; pneumothorax occurs in 18%-47%, and hemoptysis in 13%-20%. [6][7][8] Both procedures have strong and weak points, and the challenge is to combine the respective strong points of bronchoscopy and CTNB. In cases wherein the EBUS probe is adjacent to lesions, the combination of EBUS and transbronchial needle aspiration (TBNA) has been demonstrated to be useful and safe.…”
Section: Introductionmentioning
confidence: 99%